School Readiness of Preschool Children Entering Elementary School Based on Nijmeegse Schoolbekwaamheids Test (Nst) (Case Study at Early Childhood Education Al Husna Pengging Boyolali In 2017) - nur fauziyah (Early Childhood Research Journal (ECRJ), 2019)
This is descriptive research to find out school readiness in terms of N.S.T (Nijmeegse Schoolbekwaamheids Test) test results. Research uses quantitative approach. Subject of the research is students of early childhood education Al Husna Kindergarten B level in Pengging Boyolali which will enter elementary school. Number of research subject is 32 students. Measuring instrument used on the research is N.S.T (Nijmeegse Schoolbekwaamheids Test) and also observation. Analysis of data will be done quantitatively with simple statistic technique. Result of the research shows that from 32 students, 50% stated has readiness as much 16 students, 40,6% is quite ready as much 13 students meanwhile not ready is 9,4% as much 3 students.The most prominent aspect in its level of maturity is aspect of form observations and the ability to distinguish which is 84,4% for 27 students. The least aspect on the task of understanding the story is 25% for 8 students. Qualitatively, school readiness aspect from cognitive aspect is observation and the ability to distinguish, notions of big, number and comparison, concentrate and memory already reaches a fairly optimal level of maturity. Meanwhile related aspect with understanding stories and pictures of people skill the level of preparedness is not yet optimal.